The Dark Entity - Best, J.T (Certes Press, 1999)
... a strange shadow cut the setting sun in half and began to approach in the form of a huge, dark skyline. It is the dark Entity. So begins a horrible nightmare for Heinz, a windsailor. Exploring the outer reaches of Flatland, he is enveloped in an insidious black void that can suck dry the mortal essence of anything caught within its grasp. This black hell is ruled by Garghost - a semi-transparent spectre and his five ghoulish disciples. Their goal is to systematically render Heinz senseless and in so doing prepare him for the malevolence of Garghost. 'The Dark Entity' is a science-fiction fantasy about the power of evil, and one man's incredible determination to survive. -- Back Cover.